The impact of centralization on structural changes in healthcare: when it works - Shishkin, Sergey; Sheiman, Igor; Potapchik, Elena; Vlassov, Vasily; Sazhina, Svetlana (Frontiers in Health Services, 2025)
PurposeAfter a decade of post-Soviet decentralization of the healthcare in Russia the opposite trend has been dominating. This paper explores the impact of centralization of healthcare governance on the structure of the healthcare system in Russia, including shift in service delivery structure, the institutional organization of healthcare providers, and their interactions.MethodologyWe employ quantitative and qualitative analysis to study how centralization has contributed to restructuring service delivery with instruments of utilization planning, vertical health programs, and centrally determined pathways of patients flows in a multi-level health care system.FindingsCentralization of healthcare governance has contributed to restructuring the Russian healthcare system, providing positive changes in structure of inpatient/outpatient care utilization, the organizational structure of service providers, and the structure of their activities. Inpatient care is increasingly replaced by outpatient care and day wards. Centralization contributed to creation of new types of medical organizations (perinatal centers, vascular centers, etc.), development of prevention, and strengthening of providers activity integration in a multi-level system of medical care. However, centralization has not been accompanied by the effective interaction of different levels of governance in developing structural reforms and their implementation in the regions. Uniform activities for the entire country do not take into account specific regional and local conditions. Some unified solutions are implemented in regions with negative consequences for the accessibility of care locally. The excessively centralized model of preventive measures does not provide an effective balance between detection of diseases and follow-up treatment. A so-called “new primary healthcare model”, initiated from the top, limits the development of alternative models that are needed in many regions of the country. The analysis concludes with a set of conditions that should be followed in designing and implementing a centralized model of healthcare governance.